Hormonal Contraceptives and Cerebral Venous Thrombosis Risk: A Systematic Review and Meta-Analysis - Amoozegar, Farnaz; Ronksley, Paul E.; Sauve, Reg; Menon, Bijoy K. (Frontiers in Neurology, 2015)
Objectives: Use of oral contraceptive pills (OCP) has previously been shown to increase the risk of cerebral venous sinus thrombosis (CVST). Whether this risk varies by type of OCP use, duration of use and other forms of hormonal contraceptives is largely unknown. This systematic review and meta-analysis updates the current state of knowledge on these issues. Methods: We performed a search to identify all published studies on the association between hormonal contraceptive use and risk of CVST in women aged 15-50, using MEDLINE, EMBASE, Cochrane systematic review, the Cochrane Center for Clinical Trials and CINAHL. Risk of CVST was estimated using random effects models. Stratification and meta-regression were used to assess heterogeneity. Results: Of 861 studies reviewed for eligibility, quality, and data extraction, 11 were included in the final systematic review. The pooled odds of developing CVST in women of reproductive age taking oral contraceptives was over 7 times higher compared to women not taking oral contraceptives (OR=7.59, 95% CI 3.82 – 15.09). There is some indication that third generation OCPs may confer a higher risk of CVST than second generation OCPs, but this remains controversial. Data is insufficient to make any conclusions about duration of use and other forms of hormonal contraceptives and risk of CVST. Conclusions: OCP use increases the risk of developing CVST in women of reproductive age. Better studies are needed to determine if duration and type of hormonal contraceptive use modifies this risk.